Developing rapid electrochemical relithiation protocols for scalable relithiation of lithium-ion battery cathode materials - Verma, Ankit; Colclasure, Andrew M.; Coyle, Jaclyn (Frontiers in Batteries and Electrochemistry, 2023)
The recent and ongoing boom in electric vehicle sales has caused the circularity of the supply chain for electric vehicle battery materials to come under a great deal of scrutiny. Innovative recycling processes, or direct recycling, that offer the possibility of reducing the cost of recycling are one possible solution to regaining resources from end-of-life (EoL) electric vehicle batteries. Electrochemically shuttling lithium back into the cathode, or electrochemical relithiation, is a possible technique for restoring lithium content to NMC materials (EoL) in a direct recycling process. This study provides essential understanding towards developing an electrochemical relithiation protocol that will restore lithium loss in intercalation cathode materials that reach EoL by loss of lithium inventory (LLI) as opposed to other degradation mechanisms like loss of active material (LAM), cation mixing or phase transition. Electrochemically aged NMC cathode materials have been prepared and characterized to establish the extent of EoL material structural degradation and lithium loss. A model-informed experimental process is used to identify the optimal electrochemical relithiation protocol to minimize the time taken to relithiate EoL materials and maximize the amount of lithium restored. Protocols were evaluated based on their ability to enable rapid lithium intercalation, maintain structural uniformity in the EoL material and fully restore lithium content. An optimal protocol was identified at elevated temperatures utilizing a novel scanning voltage step.